The GHG emission determinants research for waste disposal process at city-scale in Baoding. (August 2020) - Lu, Can; Li, Wei; An, Changle
Highlights: Established a city-scale's systematically appraisal of greenhouse gas driving factor. Greenhouse gas emissions in different fields of a city were clearly shown. The overlapping effects of different scenarios and policies were reflected. Appropriate policies are more effective for greenhouse gases in urban waste disposal. Specific emission reduction measures were put forward for Baoding and other cities. Abstract: Current research on greenhouse gas(GHG) inventories supports the view that waste disposal is an important source of urban GHG emissions. Studying the driving factors behind the changes in greenhouse gas emissions from municipal waste treatment can provide better information support for emission reduction. This paper systematically evaluates the city-scale GHG emission determinants in waste disposal process using a system dynamics model. Subsequently, an empirical analysis was conducted on Baoding City. This research brings some interesting results: (1) The impact of the population is paramount. The emission reduction effect of controlling the size of the city and improving the quality of the population is remarkable. (2) Policy is another key factor. Comprehensive and appropriate policies are more effective than introducing and applying advanced technologies. Including urban land management, waste separation and metering and charging can be used for it. (3) It is necessary to formulate appropriate emission reduction policies for different industrial sectors by focusing on GHG generated from solid waste. Because the combined effect of factors is not equal to the simple sum of each factor. Policy implications in terms of our study results are discussed.